The Degree of Cystocele and Rectocele with Hiatal Area Levator Ani: Derajat Cystocele dan Rectocele dengan Hiatal Area Levator Ani - Fernandi Moegni; Hari Santoso (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To investigate the degree of cystocele and rectocele with a maximum of levator hiatal area (AHL) during Valsava. Methods: Secondary data analysis of 90 patients with uterine prolapse January 2012 to November 2013 in the clinic Uroginekologi RSCM, Jakarta. 3D/4D ultrasound measurement and pelvic organ prolapse system Quantification (POP-Q) stage I-IV cystocele and rectocelestage I-IV. All statistical analyses were analyzed using Stata 20 for Windows. Results: Significant difference cystocele stage I-II (n = 25) with stage III-IV (n = 65), the maximum AHL with a difference of 4.33 cm2 (p = 0.040). In rectocele stage I-II (n = 64) and stage III-IV (n = 26) of 3.85 cm2 (p = 0.130). AUC values for stage I-II and III-IV cystocele was 0.607 (IK95% from 0.467 to 0.738), and the ROC for rectocele was 0.603 (IK95% from 0.472 to 0.734). The ROC optimal cut point for cystocele stage I-II with III-IV with the highestsensitivity and specificity is 29 cm2 (0.523 sensitivity, specificity 0.520), the rectocele is 30 cm2 (0.538 sensitivity, specificity 0.584). Conclusion: There is a significant relationship between the degree of cystocele and area of the levator ani muscles when Valsava, but there is no relationship at rectocele. The value of maximum area under the curve (AUC) hiatal area of the levatorani muscle in distinguishing stage I-II and III-IV cystocele are relatively similar to rectocele stage I-II and III-IV. Optimal cut point hiatal area of the levatorani muscle in distinguishing stage I-II and III-IV cystoceleis 29 cm2, while for rectocele is 30 cm2 with sensitivity and specificity values were quite good. Keywords: cystocele, levatorani hiatal area, pelvic organ prolapse, rectocele